1971
DOI: 10.1111/j.1476-5381.1971.tb08035.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the duration of experimental fever on salicylate antipyresis in the rabbit

Abstract: Summary1. Steady state fever has been produced in rabbits with a priming injection followed by a sustaining infusion of homologous plasma containing endogenous pyrogen (EP). This fever appears to last as long as the infusion continues. 2. Intravenous salicylate given 1 h after the start of the EP infusion produced only a small antipyretic effect. The same dose of salicylate given 4 h after the start of an EP infusion resulted in rapid and progressive defervescence. Intermediate antipyretic responses were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1972
1972
1988
1988

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The failure of the salicylate to produce antipyresis confirms earlier reports of its weak antipyretic properties in rabbits (Grundman, 1969;Cranston et al 1970Cranston et al , 1971van Miert et al 1972). We have now shown that in spite of its failure to produce antipyresis, the salicylate prevented the appearance of prostaglandin in c.s.f.…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…The failure of the salicylate to produce antipyresis confirms earlier reports of its weak antipyretic properties in rabbits (Grundman, 1969;Cranston et al 1970Cranston et al , 1971van Miert et al 1972). We have now shown that in spite of its failure to produce antipyresis, the salicylate prevented the appearance of prostaglandin in c.s.f.…”
Section: Methodssupporting
confidence: 77%
“…Since the dose of leucocyte pyrogen used in our experiments was submaximal (cf. Cranston et al 1971) partial inhibition of prostaglandin synthesis might have been expected to cause partial abatement of the fever; none was observed. Veale & Cooper (1975) have recently reported that it is possible to create lesions in the brains of rabbits which render them insensitive to the hyperthermic effects of prostaglandins; they still develop fever in response to pyrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rectal temperature, measured by an indwelling thermistor, was recorded automatically at 5 min intervals. Using techniques described previously (Cranston, Luff, Rawlins & Wright, 1971) a guide tube was screwed to the skull plate. A sterilized stainless-steel cannula (0-56 nun o.d.)…”
Section: Methodsmentioning
confidence: 99%
“…There is also evidence to suggest that salicylates might exert at least part of their action within the central nervous system since injections of small doses of sodium salicylate into the lateral cerebral ventricles of rabbits with experimental fever cause rapid, dosedependent defervescence (Cranston, Luff, Rawlins & Rosendorff, 1970). Further evidence suggests that salicylates exert their central effect on temperature by competitively antagonizing the effects of endogenous pyrogen within the brain (Cranston, Luff, Rawlins & Wright, 1971). The nature of this antagonism is not known, but if salicylates exerted their effects by antagonizing endogenous pyrogen directly, they might be expected to act at the same sites within the central nervous system as endogenous pyrogen.…”
Section: Introductionmentioning
confidence: 99%